Respuesta :

Answer:

x = -60

Step-by-step explanation:

1.4(2x+3) = 0.9(3x-2)

(1.4)(2x) + (1.4)(3) = 0.9(3x) - 0.9(2)

2.8x + 4.2 = 2.7x - 1.8

2.8x - 2.7x = -1.8 -4.2

0.1x = -6

x = -60

Answer:

x = - 60

Step-by-step explanation:

1.4(2x+3) = 0.9(3x-2)                 Remove the brackets

2.8x + 4.2 = 2.7x - 1.8               Subtract 4.2 from both sides

2.8x +4.2-4.2 = 2.7x - 1.8- 4.2

2.8x = 2.7x - 6                           Subtract 2.7x from both sides

2.8x-2.7x = - 6

0.1x = - 6                                    Divide by 0.1

0.1x/0.1 = - 6/0.1

x = - 60  

ACCESS MORE